2020
DOI: 10.21203/rs.3.rs-34749/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Anemia Prevalence in Korean Older Adults, an Advent Healthcare Problem: 2007-2016 KNHANES

Abstract: BACKGROUND: Anemia is associated with high morbidity and mortality in older people. However, anemia in older individuals is not fully understood, and national data on the prevalence and characteristics of anemia in Korean older people are lacking. This study aimed to evaluate the prevalence and characteristics of anemia in older adults using data from the Korea National Health and Nutrition Examination Survey (KNHANES), which is the nation-wide cross-sectional epidemiological study conducted by Korean Ministry… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…It is a physiological finding that the prevalence of asymptomatic and mild anaemia increases in apparently healthy elderly, which is also confirmed by other studies, 12‐14 suggesting that the decrease in haemoglobin levels might be a consequence of the normal ageing process. Similarly, Phillips et al show nutritional deficiency and age‐associated renal dysfunction are not the main reason for age‐related trends 15 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is a physiological finding that the prevalence of asymptomatic and mild anaemia increases in apparently healthy elderly, which is also confirmed by other studies, 12‐14 suggesting that the decrease in haemoglobin levels might be a consequence of the normal ageing process. Similarly, Phillips et al show nutritional deficiency and age‐associated renal dysfunction are not the main reason for age‐related trends 15 .…”
Section: Discussionsupporting
confidence: 79%
“…Although haemocyte RI studies in Chinese children as well as in some regions of China have been reported 10,11 the trends of RBC parameters in these studies represented the characteristics of a certain area, young children or adults, not covered aged population nationwide. In this study, 6.47% of people aged ≥ 60 y have anaemia, which is lower than 14.0% in South Korea and 10.6% in the United States, 12 the prevalence of anaemia remains high. For better clinical decisions, such as transfusion or medical treatment for anaemia in the elderly, a specific reference interval for ageing people is required.…”
Section: Discussionmentioning
confidence: 55%